An approach towards the synthesis of Dysidamide C and its derivatives / Sharifah Edayu Syed Monudeen Khan - Syed Monudeen Khan, Sharifah Edayu (2013)
Dysidamide C was chosen in this study as the synthetic target due to its unique skeletal structure and its interesting pharmacological activities. This thesis has been divided into five main sections. Chapter one is a review on our target compounds-Dysidamide C. Chapter two focus on the synthetic strategies of compound which have similar skeleton to Dysidamide C by different research groups, whilst chapter three consists of our synthetic works. Experimental details including the spectroscopic data are provided in chapter four and finally, future works are recommended in chapter five. Our synthetic approach towards the synthesis of Dysidamide C was divided into two different routes. The first route began by couple up readily available starting material known as glycine methyl ester and methyl malonate potassium through condensation reaction followed by Dieckmann cyclisation to give pyrolidine ring known as the p,p-diketoester. Letting p,pdiketoester undergo a series of successive chemical reactions, which include demethoxycarbonylation, dialkylation at C-3 position, olefin formation at C-5, successfully gave our desire template known as methylene ketone type of compounds, 125 (with an overall yield of 21%). For the second route, methylene ketone type of compounds, 125, was obtained in four steps using methyl acetoacetate as the starting material. The first step was known as dimethylation, followed by brominations, intercyclization reaction and finally olefin formations at C-5 (with an overall yield of 26%). This entire attempt was successfully furnished us with over 35 pyrrolidine type of compounds. Apart from that, we manage to manipulate the important intermediates 125, to produce Dysidamide C-derivative known as diesterified compound and woxazoline in 4 steps. In brief, we have developed a mild and operationally simple procedure towards the synthesis of Dysidamide C. The result extracted from this study thus far may be used to develop new scientific knowledge and remarkable findings.